Integrating genomic medicine into primary care –examining perceptions of community advisory board members - Paramita Das; Whitley V. Kelley; Catanya G. Stager; Tiffany Osborne; Irene Moss; Kelly East; Samantha Whitfield; Bruce Korf; Nita Limdi; Lori Brand Bateman (Journal of Community Genetics, 2026)
The Alabama Genomic Health Initiative (AGHI), funded by the state of Alabama, aims to provide genomic testing, interpretation, and counseling free of charge to Alabama residents. A 14-member Community Advisory Board (CAB) was convened in 2021 to provide community insight on integrating genomic medicine into clinical care and assessing future perspectives. The CAB was comprised of members from diverse ethnic backgrounds and represented a wide range of age groups, with balanced gender representation from two Alabama counties. The CAB met quarterly, and the team explored the perceptions of members related to genomic medicine through qualitative inquiry with exploratory quantitative findings. Self-administered pre- and post-surveys, completed prior to the first CAB meeting (pre) and after meeting five (post), were utilized to evaluate positive and negative views towards the future of genomic medicine. Five meetings were conducted in a focus group format, and transcripts were coded and analyzed to identify emerging themes. Ten of fourteen (71%) CAB members completed both surveys. Results indicate there was a slight shift in responses related to the future of genomic medicine from pre to post-test, but no significant changes were noted. Eleven of fourteen (80%) CAB members attended four out of five meetings. The prominent themes included barriers to genomic testing, strategies for recruitment, and recommendations for sharing test results. Members believed that participation in the CAB facilitated acquiring new knowledge and insight on genomic medicine.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Viral load differences associated with infection outcomes and resistance to white spot syndrome virus (WSSV) infection in mud crab, Scylla serrata - Angela Camille Aguila-Toral; Gardel Xyza L. Silvederio; Dan Joseph Logronio; Kelly S. Bateman; Grant D. Stentiford; Edgar C. Amar; Rachel Ravago-Gotanco (Journal of Invertebrate Pathology, 2026)

The first report of Hematodinium perezi genotype I infection of Chinese mitten crab (Eriocheir sinensis) from the River Thames, UK - Rose C. Kerr; Hamish J. Small; David Bass; Wafa S. Al Arimi; Stuart Ross; Roland Pevsner; Bryony Williams; Ronny van Aerle; Grant Stentiford; Kelly Bateman (Journal of Invertebrate Pathology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Identification of Albopleistophora grylli n. gen. n. sp. (Microsporidia) and its impact on crickets (Gryllus spp.) in food-and-feed culture systems - Edouard Bessette; Jamie Bojko; Kelly S. Bateman; Stuart Ross; Nicolai V. Meyling; Bryony A.P. Williams (Journal of Invertebrate Pathology, 2025)

Re-examination of archived materials reveals infection of zebra mussels Dreissena polymorpha in UK waters with the parasite Haplosporidium raabei - Rachel Foster; Jasmine E. Hunt; Kelly S. Bateman; Matthew J. Green; William Ball; Matt Longshaw; Laura Heath; Paul Stebbing; Georgia M. Ward (Biological Invasions, 2025)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Salinity and temperature affect the symbiont profile and host condition of Florida USA blue crabs Callinectes sapidus - Erin A. Walters; Jamie Bojko; Claire E. Crowley; Ryan L. Gandy; Charles W. Martin; Colin P. Shea; Kelly S. Bateman; Grant D. Stentiford; Donald C. Behringer (Journal of Invertebrate Pathology, 2023)

Pseudohepatospora borealis n. gen. n. sp. (Microsporidia: Enterocytozoonida): A microsporidian pathogen of the Jonah crab (Cancer borealis) - Jamie Bojko; Donald C. Behringer; Kelly S. Bateman; Grant D. Stentiford; K. Fraser Clark (Journal of Invertebrate Pathology, 2023)

Diseases of the giant river prawn Macrobrachium rosenbergii : A review for a growing industry - Chantelle Hooper; Partho P. Debnath; Grant D. Stentiford; Kelly S. Bateman; Krishna R. Salin; David Bass (Reviews in Aquaculture, 2023)
The giant river prawn, Macrobrachium rosenbergii , is a major focus of aquaculture in tropical and sub‐tropical regions around the globe. Over the last 30 years, culture of M . rosenbergii has increased exponentially as demand has risen both for domestic consumption and for international export trade. As with many aquaculture species increases in production have been accompanied by the emergence of diseases affecting yield, profit and trading potential. Disease‐causing agents include pathogens infecting other crustaceans, such as Decapod Iridescent Virus (DIV1), as well as pathogens only known from M . rosenbergii such as White Tail Disease caused by Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV). Here, we review the pathogenic agents associated with the culture of M . rosenbergii since commercial culture began in earnest during the 1970s. Particular emphasis is given to pathogens first identified in other aquaculture host species, but which have subsequently been shown to infect and cause disease in M . rosenbergii . As polyculture of M . rosenbergii with other aquaculture species is common practice, including culture with other decapods, crabs and fish, increased pathogen transfer among these farmed species may occur as M . rosenbergii aquaculture increases in the future.

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Establishment and characterization of a platinum- and paclitaxel-resistant high grade serous ovarian carcinoma cell line - Pang-Ning Teng; Nicholas W. Bateman; Guisong Wang; Tracy Litzi; Brian E. Blanton; Brian L. Hood; Kelly A. Conrads; Wei Ao; Kate E. Oliver; Kathleen M. Darcy; William P. McGuire; Keren Paz; et al. (Human Cell, 2017)

Decay of the glycolytic pathway and adaptation to intranuclear parasitism within Enterocytozoonidae microsporidia - Dominic Wiredu Boakye; Pattana Jaroenlak; Anuphap Prachumwat; Tom A. Williams; Kelly S. Bateman; Ornchuma Itsathitphaisarn; Kallaya Sritunyalucksana; Konrad H. Paszkiewicz; Karen A. Moore; Grant D. Stentiford; Bryony A. P. Williams (Environmental Microbiology, 2017)
Summary Glycolysis and oxidative phosphorylation are the fundamental pathways of ATP generation in eukaryotes. Yet in microsporidia, endoparasitic fungi living at the limits of cellular streamlining, oxidative phosphorylation has been lost: energy is obtained directly from the host or, during the dispersive spore stage, via glycolysis. It was therefore surprising when the first sequenced genome from the Enterocytozoonidae – a major family of human and animal‐infecting microsporidians – appeared to have lost genes for glycolysis. Here, we sequence and analyse genomes from additional members of this family, shedding new light on their unusual biology. Our survey includes the genome of Enterocytozoon hepatopenaei , a major aquacultural parasite currently causing substantial economic losses in shrimp farming, and Enterospora canceri , a pathogen that lives exclusively inside epithelial cell nuclei of its crab host. Our analysis of gene content across the clade suggests that Ent. canceri 's adaptation to intranuclear life is underpinned by the expansion of transporter families. We demonstrate that this entire lineage of pathogens has lost glycolysis and, uniquely amongst eukaryotes, lacks any obvious intrinsic means of generating energy. Our study provides an important resource for the investigation of host‐pathogen interactions and reductive evolution in one of the most medically and economically important microsporidian lineages.

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Are selective serotonin re-uptake inhibitors associated with an increased risk of self-harm by antidepressant overdose? - D. N. Bateman; J. Chick; A. M. Good; C. A. Kelly; G. Masterton (European Journal of Clinical Pharmacology, 2005)

Electrocardiogram and cardiovascular changes in thioridazine and chlorpromazine poisoning - E. M. Strachan; C. A. Kelly; D. N. Bateman (European Journal of Clinical Pharmacology, 2004)

Are selective serotonin re-uptake inhibitors associated with an increased risk of self-harm by antidepressant overdose? - D. N. Bateman; J. Chick; A. M. Good; C. A. Kelly; G. Masterton (European Journal of Clinical Pharmacology, 2004)